2D modelling of inclined intergranular stress corrosion crack paths. Issue 4 (13th October 2016) - Griggs, J; Gamboa, E; Lavigne, O
Abstract: Inclined high pH stress corrosion cracking (SCC) is a type of intergranular environmental cracking in gas pipelines, which differs from typical SCC by propagating at an angle from the wall direction. Investigations of Australian and Canadian inclined SCC colonies have not provided a clear indicator of a cause for the abnormal crack growth direction. This paper addresses the possibility of crack tip strain enhanced electrochemistry causing the inclination. Potentiodynamic tests were conducted to quantify the influence of strain on the electrochemistry, and strain was found to increase current density up to 300% in the SCC region. A model was developed that incorporates crack tip strain driven SCC growth, which showed good agreement with field grown cracks, and the aspect ratio of the grains was shown to have an effect on the inclination angle. The results indicate that crack tip strain enhanced electrochemistry is a plausible cause for inclined SCC.